2021
DOI: 10.3390/ijerph18158116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Summer Sunshine Exposure on Vitamin D Status in Young and Middle Age Poles: Is 30 ng/mL Vitamin D Cut-Off Really Suitable for the Polish Population?

Abstract: Background: There is no consensus regarding vitamin sufficiency status with either 20 ng/mL or 30 ng/mL sufficiency cut-off. We assessed the effects of summer sunshine exposure on vitamin D status. Participants: We measured vitamin D concentrations, PTH, creatinine, and total calcium in 132 healthy subjects, age 29.36 ± 13.57 years, in spring and autumn. Results: There was an overall increase in vitamin D concentrations from spring to autumn from 18.1 ± 7.39 ng/mL to 24.58 ± 7.72 ng/mL, (p < 0.001), accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…We demonstrated that only subjects with severe 25OHD deficiency (<12 ng–30 nmol/L) were at an increased risk of subsequent COVID-19 infection, while it was no longer significant for concentrations above 20 ng/mL (50 nmol/L), i.e., a concentration considered sufficient by the Institute of Medicine [ 12 ]. In our previous study [ 15 ] we conclusively demonstrated that the majority of healthy individuals aged 6–50, in latitudes similar to Poland (49° to 54° N), obtain concentrations of 25OHD > 20 ng/mL in autumn without any supplementation, particularly if they have at least a two-week holiday period in summer. This observation clearly does not preclude the need for vitamin D supplementation in a selected group of subjects, e.g., in elderly obese individuals [ 25 ], or as an adjunct treatment in weight-loss programs [ 26 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We demonstrated that only subjects with severe 25OHD deficiency (<12 ng–30 nmol/L) were at an increased risk of subsequent COVID-19 infection, while it was no longer significant for concentrations above 20 ng/mL (50 nmol/L), i.e., a concentration considered sufficient by the Institute of Medicine [ 12 ]. In our previous study [ 15 ] we conclusively demonstrated that the majority of healthy individuals aged 6–50, in latitudes similar to Poland (49° to 54° N), obtain concentrations of 25OHD > 20 ng/mL in autumn without any supplementation, particularly if they have at least a two-week holiday period in summer. This observation clearly does not preclude the need for vitamin D supplementation in a selected group of subjects, e.g., in elderly obese individuals [ 25 ], or as an adjunct treatment in weight-loss programs [ 26 ].…”
Section: Discussionmentioning
confidence: 76%
“…The one-year observation period was also a limitation, but this was related to the introduction of the universal COVID-19 vaccination program in Poland, which altered the relationship between vitamin D sta8tus and the potential risk of COVID-19 infection. Although our study was not designed to address the issue of vitamin supplementation, in view of our previous findings [ 15 ], we can suggest that among healthy individuals age 6–50 there is no need to take any 25OHD supplements for COVID-19 prevention if their 25OHD concentrations are above 20 ng/mL, while such levels can be successfully obtained through lifestyle measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum vitamin D status was classified into three groups according to the serum 25-hydroxyvitamin D level: deficient (<20 ng/mL), insufficient (20–30 ng/mL), and sufficient (>30 ng/mL). 8…”
Section: Methodsmentioning
confidence: 99%
“…The serum vitamin D status was classified into three groups according to the serum 25-hydroxyvitamin D level: deficient (<20 ng/mL), insufficient (20-30 ng/mL), and sufficient (>30 ng/mL). 8 The data were statistically analyzed using the Wilcoxon rank-sum test, chi-square test, and t test as appropriate. A P value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%